ANALISIS IMPLIKATUR PERCAKAPAN PADA FILM “LOSMEN BU BROTO” KARYA EDDIE CAHYONO DAN IFA ISFANSYAH - Yessi Tanjung; Putri Putri; Salsabila Salsabila; Angel Marbun; Sita G Br Pandia; Lasenna Siallagan (Asosiasi dosen IDEBAHASA KEPRI, 2023)
This study aims to describe the conversational implicature contained in the film entitled Losmen Bu Broto. This study used descriptive qualitative method which describes the situations or phenomena occuring with scientific methods to solve real problems. The data used in this study were conversations in the film Losmen Bu Broto by Eddie Cahyono and Ifa Isfansyah. The data were analyzed in 4 stages, namely identification, reduction, classification, and data interpretation. The results of the study showed that there were 16 implicature data in the film entitled Losmen Bu Broto consisting of 7 assertive speech data, 3 directive speech data, 5 expressive speech data, and 1 declarative speech data. The most common speech act in this film was assertive speech act. Meanwhile, commissive speech was not found in this study.